Linearyzacja sił sprężystych w układzie wibrouderzeniowym - Cempel, C. (Engineering Transactions, 1969)
This work is an attempt of the linearization of the elastic forces in vibration system with percussion. The percussion characteristics obtained in this way were compared with characteristics obtained by the method of adaptation of the equations. It was shown this way that the linearization of vibro-percussion system performed is correct and maps all its features exactly.